Formulasi Sediaan Eyeshadow Compact Powder Ekstrak Kunyit (Curcuma domestica Val): Formulation of Eyeshadow Compact Powder Turmeric Extract (Curcuma domestica Val) - Sari, Ananda Alfira; Saryanti, Dwi (Jurnal Sains dan Kesehatan, 2025)
Eyeshadow compact powder is a solid-shaped cosmetic that can give color to the eyelids aiming to give a firm impression on the user. Synthetic dyes are still often used in cosmetics because they are bright but harmful in color. The curcumin compound in turmeric (Curcuma domestica Val.) makes it an alternative to the natural yellow dye. This study aims to utilize turmeric dye as a natural dye for eyeshadow compact powder and determine its stability. The method used in making extracts is the maceration method of 96% ethanol extract solvent. The concentration of eyeshadow compact powder turmeric extract is 5%, 10%, and 15%. The parameters tested include organoleptic, homogeneity, pH, dispersion, cracking, polishing, stability, and hedonic tests. The results of the three eyeshadow compact powder formulas meet the requirements in organoleptis tests, homogeneity, dispersion, polishing power, hedonic tests, and pH tests. The results of the 15% concentration of turmeric extract compact powder eyeshadow showed physical properties including dark yellow color, compact powder form, turmeric odor strong, homogeneous, dispersed, and pH test of (6.9±0.1), polishing test of (1.3±0.57), and hedonic test most preferred by panelists. Keywords:          Eyeshadow Compact Powder, Curcumin, Turmeric, Natural Dyes   Abstrak Eyeshadow compact powder merupakan kosmetik berbentuk padat yang dapat memberikan warna pada kelopak mata bertujuan untuk memberikan kesan tegas pada pengguna. Pewarna sintetis masih sering digunakan dalam kosmetik karena warnanya cerah namun berbahaya. Senyawa kurkumin didalam kunyit (Curcuma domestica Val.) menjadikannya suatu alternatif pewarna yang alami berwarna kuning. Penelitian ini bertujuan untuk memanfaatkan pewarna kunyit sebagai pewarna alami eyeshadow compact powder dan mengetahui stabilitasnya. Metode yang digunakan pada pembuatan ekstrak yaitu metode maserasi pelarut ekstrak etanol 96%. Konsentrasi eyeshadow compact powder ekstrak kunyit yaitu 5%, 10%, dan 15%. Parameter yang diuji meliputi uji organoleptik, homogenitas, pH, daya sebar, keretakan, poles, stabilitas, dan hedonic. Hasil ketiga formula eyeshadow compact powder memenuhi persayaratan pada uji organoleptis, homogenitas, dispersi, daya poles, uji hedonic, dan uji pH. Hasil penelitian eyeshadow compact powder ekstrak kunyit konsentrasi 15% menunjukkan sifat fisik antara lain warna kuning tua, bentuk compact powder, bau kunyit kuat, homogen, terdispersi, dan uji pH sebesar (6,9±0,1), uji poles sebesar (1,3±0,57), dan uji hedonik yang paling disukai panelis. Kata Kunci:         Eyeshadow Compact Powder, Kurkumin, Kunyit, Pewarna Alami